Tinjauan Hukum Islam terhadap Pembulatan Pengurangan Timbangan Jual Beli Tembakau di Gudang Jasa-Jasa - Rokhmat; Eko Santoso; Hidayatun Ulfa (Yayasan Azhar Amanaa Yogyakarta, 2023)
The rounding of tobacco trade scales is a manifestation of the daily relationship between sellers and buyers during the tobacco season. As known, Islam mandates fair trade practices without any element of ambiguity, deception, usury, and the like. Buying and selling are social practices to meet livelihood needs. The tobacco trade practices in the Tlahab Village warehouse services are conducted directly, and transactions are based on mutual trust between the consumers and the merchants. However, upon re-weighing, it's found that the weight is less than the initial weight due to discrepancies between the agreed-upon terms at the beginning. The formulation of the problems based on this issue is: how is the practice of rounding in the reduction of tobacco trade scales carried out? What is the Islamic legal perspective on the practice of rounding in the reduction of tobacco trade scales in Tlahab Village, Kledung Sub-district?This research is a normative-empirical study employing a qualitative approach. Data were collected using primary and secondary sources through observation, interviews, and documentation. The collected data were analyzed using descriptive analysis methods. The results of this study show that, firstly, the practice of rounding in the reduction of tobacco trade scales in Tlahab Village is essentially conducted using the same contract as typical trade agreements. In this trade practice, communication between the seller and buyer is direct without intermediaries. Merchants make purchases as usual, and transactions are based on mutual trust between consumers and merchants. Secondly, the Islamic legal perspective on rounding in the reduction of tobacco trade scales indicates that this practice is not allowed because it only benefits the merchants, leading to ambiguity or gharar in tobacco weighing, thereby resulting in injustice to sellers or farmers.